Interface functionalization of mesoporous ruthenium films with polyaniline for enhanced hydrogen evolution electrocatalysis at all pH values. Issue 27 (24th June 2022) - Duan, Zhongyao; Zhang, Mei; Cui, Lin; Yu, Hongjie; Deng, Kai; Xu, You; Wang, Ziqiang; Wang, Liang; Wang, Hongjing
Abstract : mRu@PANI/CP has been synthesized for pH-universal hydrogen evolution electrocatalysis with excellent electrocatalytic performance. Abstract : The design of electrocatalysts with favorable morphologies and surface compositions is an effective strategy to prepare electrocatalysts for the hydrogen evolution reaction (HER). Herein, a polyaniline (PANI) modified mesoporous ruthenium film supported on carbon paper (mRu@PANI/CP) was successfully synthesized by a two-step electrodeposition method at room temperature. With the mesoporous film structure and PANI modification, mRu@PANI/CP displayed superior HER catalytic activity with overpotentials of 30 mV (0.5 M H2 SO4 ), 27 mV (1.0 M KOH), and 24 mV (1.0 M PBS), respectively, at a current density of 10 mA cm −2 . This work not only provides a powerful route to prepare a mesoporous Ru film, but also offers a useful interface functionalization strategy to further enhance its electrocatalytic performance, beyond the HER.